PENGARUH ASBÂB AL-WURÛD HADIS TERHADAP PEMAHAMAN HUKUM - Nasir, Muhammad (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2023)
AbstractThe Hadith of the Prophet as one of the two largest sources of Islam has a very important influence in determining Islamic law. Knowing the asbab al-wurud is the best way to understand the meaning of hadith correctly, so that we can properly ground it in our behavior. Also it is an important science in showing the relationship of text with reality. Or in other words it is the social context for the text (hadith).